Charophytes for description and monitoring of inland waters in Sicily - Troia, Angelo; Barone, Rossella
The island of Sicily, in the center of the Mediterranean basin, is a well-known biodiversity hotspot (Médail & Quézel, 1997). Unfortunately, the knowledge of its charophyte flora is absolutely unsatisfactory. The few available data derive from some scattered phytosociological works and some articles published more than 100 years ago. According to the last national synthesis (Bazzichelli & Abdelahad, 2009) a total of 19 Charophytes species should occur in the island, distributed in 4 genera: Chara L. (11), Nitella Agardh (5), Tolypella (A. Braun) A. Braun (2) and Lamprothamnium J. Groves (1). However an updated list of the species occurring in the island, together with their distributions, is currently lacking. It is noteworthy that, owing to this lack of local knowledge about charophytes, information currently available on these habitats occurring in the sites of the Natura 2000 network in Sicily is absolutely insufficient. We think that the group deserves a better knowledge, both for taxonomic, biogeographic and “pure” science, and for “applied” aspects connected with water quality and biodiversity conservation, also according to important European Directives (2000/60/CE and 92/43/EEC, respectively). So our work started, gathering data and making preliminary surveys. During the preliminary investigations, charophytes have been found in both freshwater and brackish waters, from 0 to 1400 m a.s.l. In particular, Chara vulgaris L. and Lamprothamnium papulosum (Wallr.) J. Groves have been identified in different coastal seasonally flooded habitats, referred to the priority habitat “1150* coastal lagoons” according to the mentioned 92/43 Directive. Chara contraria A. Braun ex Kütz. has been identified in springs and streams, referred to the habitat “3140 Hard oligo-mesotrophic waters with benthic vegetation of Chara spp.”. Other species have been found in other habitat types, such as the priority habitat “3170* Mediterranean temporary ponds”. Médail and Quézel (1997). Annals of the Missouri Botanical ...